Temporal evolution of roof collapse from tephra fallout during the 2021-Tajogaite eruption (La Palma, Spain) - Reyes-Hardy, María-Paz; Biass, Sébastien; Dominguez, Lucia; Di Maio, Luigia Sara; Frischknecht, Corine; Bonadonna, Costanza; Pérez, Nemesio (Frontiers in Earth Science, 2024)
Although dominantly effusive, the 2021 Tajogaite eruption from Cumbre Vieja volcano (La Palma, Spain) produced a wide tephra blanket over 85 days of activity. About one month after the eruption onset, clean-up operations were implemented to mitigate the impact of tephra load on primary buildings. Here, we present a post-event impact assessment of 764 primary buildings, which expands our empirical knowledge of building vulnerability to tephra fallout to include impacts from long-lasting eruptions. Field observations are analyzed in the perspective of existing fragility curves, high-resolution satellite imagery and a reconstruction of the spatio-temporal evolution of the tephra blanket to characterize the evolution of roof collapse due to static loads over time. Thanks to a chronological correlation between the temporal evolution of tephra sedimentation and the timing of clean-up operations, we quantified their effectiveness in mitigating roof collapse. If no clean-up measures had been taken 11% of the surveyed buildings would have exceeded a 75% probability of roof collapse, while only 10 roof collapses have been observed (1.3% of the analysed buildings). This work provides key insights for further development of emergency plans for the management of long-lasting eruptions characterised by the sustained emission of tephra over weeks to months.